Multimedia and E-Learning Innovations in Developing Tolerance in a Pandemic Era: Lessons from Pangandaran - Mulyana, Asep; Mundayat, Aris Arif; Sukmajati, Mada (Nusantara Science and Technology Proceedings, 2021)
The spread of the Covid-19 virus has prompted the government to carry out various restrictions on social mobility, including closing schools. Recent studies have demonstrated the dynamics and problems in online learning, but very few of them reveal innovative online learning best practices. This article analyzes the innovation of multimedia learning and e-learning at SMK Bakti Karya Parigi (SBK), Pangandaran, in developing tolerance. Through phenomenology as a research strategy, the object of research is approached by giving space for experience-based subjectivity. Meanings, attitudes, beliefs, and emotions are important data components. Based on nine months of observations and in-depth interviews with stakeholders, this article discusses how multimedia learning and e-learning innovations are built during a pandemic. The results of this study indicate that this school has developed innovative programs, including the Vocational Balancing Program (VBP). Through VBP, SBK students interact in assisting Small and Medium-sized Enterprises (SMEs) in local villages to integrate with the online marketplace. They build creative content that promotes these SMEs amid the sluggishness due to the pandemic. The learning process that involves the dissemination of knowledge, discourse, experience, consciousness, and emotions is what breeds tolerance among SBK students. This study makes a theoretical contribution to the important role of knowledge and discourse, the function of consciousness and emotion, and the workings of discursive practice in the formation of educational subjects.